Reprodução de peixes (Osteichthyes) em afluentes do reservatório de Volta Grande, Rio Grande, Sudeste do Brasil - Braga, Francisco Manoel de Souza [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2001)
The most abundant species caught in the tributaries of the Volta Grande dam, Buriti, Divisa and Água Comprida streams were Plagioscion squamosissimus (Heckel, 1840), Pimelodus maculatus Lacépède 1803, Myleus tiete (Eigenmann & Norris, 1900), Astyanax bimaculatus (Linnaeus, 1758) and A. fasciatus (Cuvier, 1819). Plagioscion squamosissimus and Pimelodus maculatus do not have reproduction activity in the area, they just use the creeks to food and growth. Myleus tiete and Astyanax bimaculatus use the area to reproduction whereas A. fasciatus uses it to reproduction, food and growth.
Fishes reproduction in the Volta Grande dam tributaries, Grande River, Southeastern Brazil
Keywords: Reproduction; Volta Grande dam; reservoir